Outcomes of Silicone Oil Removal in Complex Retinal Detachment - Shah, Ritesh; Byanju, Raghunandan; Pradhan, Sangita (Nepalese Journal of Ophthalmology, 2018)
Introduction: Pars plana vitrectomy in combination with intraocular tamponade with silicone oil is a standard technique in the treatment of complex retinal detachment. Although the use of silicone oil has improved the results of retinal detachment surgery, its removal is recommended due to the ocular complications related to its long term use. However, retinal redetachment can occur after silicone oil removal. Objective: To evaluate the anatomical and visual outcome after silicone oil removal (SOR) in eyes with complicated retinal detachment. Material and Methods: We retrospectively analyzed 64 eyes of 64 consecutive patients of silicone oil removal over a period of 12 months. All eyes had undergone standard 3 ports pars plana vitrectomy with silicone oil placement for complicated retinal detachment. Cases that completed at least 1 month follow up duration after SOR were included in the study. Anatomical success after SOR was achieved in 56 of 64 eyes (87.5%). Seven of 8 redetachments (87.5%) were seen in eyes with silicone oil tamponade duration of less than 6 months. Visual acuity improved or was stabilized in 49 of 64 eyes (76.6%). Using paired T-test, it was found that there was no significant difference in pre and post SOR visual acuity. Postoperative ocular hypertension, corneal decompensation, band shaped keratopathy and hypotony was observed in 9.4%, 4.7%, 6.4% and 21.9% respectively. Conclusion: Although there was no significant improvement in visual acuity, redetachment and complication rates were comparable to other studies. The duration of endotamponade was not significantly associated with the redetachment rate. Key words: Silicone oil removal, Redetachment, Visual outcome, Keratopathy, ocular hypertension.